The Influence Of Korean Wave, Price Perception, And Perceived Quality On Repurchase Intention: The Mediating Role Of Customer Satisfaction In Indomie Korean Ramyeon - Stephani Priska Aichen; Giriati Giriati; Wenny Pebrianti; Heriyadi Heriyadi; Ahmadi Ahmadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Indomie Korean Ramyeon was introduced in response to the high consumption of instant noodles and the growing popularity of Korean culture in Indonesia. Increasing market competition requires companies to understand the key factors that drive consumers’ repurchase intention. This study aims to analyze the influence of Korean Wave, Price Perception, and Perceived Quality on Repurchase Intention, with Customer Satisfaction as a mediating variable. A quantitative approach was employed using an online survey of 200 respondents who had previously consumed the product. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4, and mediation effects were tested using bootstrapping. The results indicate that Korean Wave, Price Perception, and Perceived Quality have positive and significant effects on both Customer Satisfaction and Repurchase Intention. Furthermore, Customer Satisfaction mediates the relationship between Price Perception and Perceived Quality on Repurchase Intention, but does not mediate the effect of Korean Wave. These findings suggest that the Korean Wave acts as a direct driver of repurchase intention, while customer satisfaction is more strongly influenced by perceived price and product quality. Therefore, companies should maintain product quality and price-value alignment while leveraging Korean cultural trends as a marketing strategy to enhance repurchase intention.